Wielowartościowe całki stochastyczne względem semimartyngału i ich zastosowania w teorii inkluzji stochastycznych - Syga, Joachim
Properties of set-valued stochastic integrals with respect to a semimartingale are the subject of the study contained in this dissertation. Some of these properties are used to the theory of stochastic inclusions. There are considered an Itô-type and a Stratonovich-type stochastic integrals. The dissertation is devided into four chapters.
Keywords: inkluzja stochastyczna typu Itô / typu Stratonowicza; wielowartościowa całka stochastyczna typu Itô / typu Stratonowicza; proces całkowo dekomponowalny (rozkładalny); proces odwracalny; proces z czasem odwróconym; wielowartościowy proces stochastyczny; semimartyngał odwracalny